Handbook of seismic risk analysis and management of civil infrastructure systems - Tesfamariam, S.; Goda, Katsu (Woodhead Publishing in materials., 2013)
Earthquakes represent a major risk to buildings, bridges and other civil infrastructure systems, causing catastrophic loss to modern society. Handbook of seismic risk analysis and management of civil infrastructure systems reviews the state of the art in the seismic risk analysis and management of civil infrastructure systems. Part one reviews research in the quantification of uncertainties in ground motion and seismic hazard assessment. Part twi discusses methodologies in seismic risk analysis and management, whilst parts three and four cover the application of seismic risk assessment to buildings, bridges, pipelines and other civil infrastructure systems. Part five also discusses methods for quantifying dependency between different infrastructure systems. The final part of the book considers ways of assessing financial and other losses from earthquake damage as well as setting insurance rates. Handbook of seismic risk analysis and management of civil infrastructure systems is an invaluable guide for professionals requiring understanding of the impact of earthquakes on buildings and lifelines, and the seismic risk assessment and management of buildings, bridges and transportation. It also provides a comprehensive overview of seismic risk analysis for researchers and engineers within these fields. This important handbook reviews the wealth of recent research in the area of seismic hazard analysis in modern earthquake design code provisions and practicesExamines research into the analysis of ground motion and seismic hazard assessment, seismic risk hazard methodologiesAddresses the assessment of seismic risks to buildings, bridges, water supply systems and other aspects of civil infrastructure.